Variation of the mechanical properties of a soil at different states of saturation - Muñoz Perez, Sócrates Pedro (Ingeniería Solidaria, 2021)
Introduction: This article is the product of the research “Variation of the mechanical properties of a soil at different states of saturation”, developed at the National University of San Agustín, located in the city of Arequipa and carried out during 2016. Problem: In most urban areas the water table is below the foundation level; therefore, the soil is dry or partiall saturated. In such areas, it is necessary to perform tests to obtain the geotechnical parameters of the soil, taking into account the degree of saturation of the soil. Objective: To perform one-dimensional consolidation and direct shear tests at different percentages of saturation. Methodology: To characterize the mechanical properties of a soil according to its saturation state, carrying out 4 unidimensional consolidation tests at different saturation percentages of 0.00%, 65.71%, 80.56% and 100% and 4 direct cutting tests at different saturation percentages of 0.00%, 20%, 40% and 100%. For these tests, unaltered clay samples were extracted. Results: The results obtained from the mechanical characterization at different degrees of saturation influence the resistance to settlement and shear of the soil. Taking that into account, when comparing both resistances of the soil under study, the resistance to deformation decreased more than the resistance to shear. Conclusions: When comparing soils, considering that the geotechnical parameters of the soils at each degree of saturation vary considerably, it is important to perform mechanical tests to the soil, taking into account the natural moisture and not to test them in their critical or saturated state because their mechanical properties will be different, and this will directly affect the design of the foundations of the structure and, therefore, in the final cost of it. Originality: For the calculation of the mechanical parameters of the soil, the regulations describe that it should be done when the soil is in its saturated state, but the mechanical properties of the soil vary at different states of saturation. For this reason, this research reveals the change that occurs in the mechanical properties of the soil when it is dry to when it is saturated. Limitations: the model did not consider the influence of the contractile membrane to obtain the results of the geotechnical parameters studied.